Imagining Asia in the Americas - Rivas, Zelideth María, 1979-; Lee-DiStefano, Debbie (Book collections on Project MUSE., 2016)
"This book introduces and explores Asian communities in the U.S., the Caribbean, and Latin America through literary, historical, and theoretical frameworks by bringing together the multiple cultural perspectives of an emerging field of study: the transnational field of Asians in the Americas. The new scholarship of these authors addresses familial, historical, and literary ties to Asia, while also introducing the contributions of Asians in the Americas in an interdisciplinary framework, easily accessible to students and scholars and amendable for course adoption. The subjects of these essays emphasize community by discussing identity, religion, culture, public health, business, language, film, and literature. They imagine the homeland and the possibilities that life in the country of residence holds. This volume seeks to understand the historically collapsed notion of Asians in the Americas, wherein Asian identity has been strategically invoked within rigid confines for political and ideological perspectives. Through a comparative framework, Imagining Asia in the Americas moves past research models that consider the immigrant as a static subject that cuts his ties with the homeland and immerses himself in a new identity specifically linked to the host country. Instead, they introduce new approaches to examine the intersections of the past and present in community formation as it is linked to the homeland as well as the resident country"--Provided by publisher.